Therapeutic uses of epicatechin in diabetes and cancer - Abdulkhaleq, Layth Abdulmajeed; Assi, Mohammed Abdulrazzaq; Noor, Mohd Hezmee Mohd; Abdullah, Rasedee; Saad, Mohd Zamri; Taufiq-Yap, Yun Hin (Veterinary World, 2017)
Epicatechin is a natural flavonoid found in green tea. It has been reported to possess an immense antioxidant effect which contributes to its therapeutic effect against a handful of ailments. In this review, we discuss its therapeutic role in the management of two of the most important human diseases; diabetes and cancer. The consumption of epicatechin has been shown to reduce blood glucose levels in diabetic patients, while is anticancer effect was attributed to its antioxidant properties, antiangiogenic and direct cytotoxicity to cancer cells. Although the exact mechanism of action of epicatechin is still being explored, there is no doubt that it is a promising candidate as an alternative. The significance of this review is to highlight the importance of the usage of natural products (in this case, epicatechin) as an alternative for the treatment of two potentially fatal diseases which is diabetes and cancer. The aim of this review is to educate the scientific community on the role of epicatechin in ameliorating the effects of diabetes and cancers on human while understanding the potential mechanisms of these aforementioned effects.